2021
DOI: 10.1101/2021.05.19.444887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures of the human cholecystokinin receptors in complex with agonists and antagonists

Abstract: Cholecystokinin receptors, CCKAR and CCKBR, are important neuro-intestinal peptide hormone receptors and play a vital role in food intake and appetite regulation. Here we report three crystal structures of the human CCKAR in complex with different ligands, including one peptide agonist and two small-molecule antagonists, as well as two cryo-electron microscopy structures of CCKBR-gastrin in complex with Gi2 and Gq, respectively. These structures reveal the recognition pattern of different ligand types and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Recently, cryo-electron microscopy confirmed that the 17 amino acid long hormone gastrin-17 indeed forms a β-hairpin structure upon binding to CCK 2 R with the five C -terminal residues inserting deeply into the binding pocket of CCK 2 R 42 . Furthermore, the N -terminal section of gastrin-17 also orientates into a shallow binding cavity of CCK 2 R 42 .…”
Section: Methods Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, cryo-electron microscopy confirmed that the 17 amino acid long hormone gastrin-17 indeed forms a β-hairpin structure upon binding to CCK 2 R with the five C -terminal residues inserting deeply into the binding pocket of CCK 2 R 42 . Furthermore, the N -terminal section of gastrin-17 also orientates into a shallow binding cavity of CCK 2 R 42 .…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…Interestingly, Peggion and coworkers also demonstrated that Glu-residues at positions 1 and 2 of des-Trp 1 ,Nle 2 -MG form hydrogen bonds to Glu residues 5 and 6, to form the anticipated α-helical structure of N-terminus [40]. Recently, cryo-electron microscopy confirmed that the 17 amino acid long hormone gastrin-17 indeed forms a β-hairpin structure upon binding to CCK2R with the five C-terminal residues inserting deeply into the binding pocket of CCK 2 R [42]. Furthermore, the N-terminal section of gastrin-17 also orientates into a shallow binding cavity of CCK 2 R [42].…”
Section: Competition Binding Studiesmentioning
confidence: 99%
“…This is done by utilizing the molecular basis underlying the receptors' selectivity. In order to perform its essential activities, such as controlling insulin secretion and sustaining beta-cell functioning [10]. The CCK hormone must connect to certain ).…”
mentioning
confidence: 99%